Repurposing of FDA Approved Drugs Against SARS-CoV-2 Papain-Like Protease: Computational, Biochemical, and in vitro Studies - Kulandaisamy, Rajkumar; Kushwaha, Tushar; Dalal, Anu; Kumar, Vikas; Singh, Deepa; Baswal, Kamal; Sharma, Pratibha; Praneeth, Kokkula; Jorwal, Pankaj; Kayampeta, Sarala R.; Sharma, Tamanna; Maddur, Srinivas; et al. (Frontiers in Microbiology, 2022)
The pandemic caused by SARS-CoV-2 (SCoV-2) has impacted the world in many ways and the virus continues to evolve novel variants with the ability to cause frequent global outbreaks. Although the advent of the vaccines abated the global burden, they were not effective against all the variants of SCoV-2. This trend warrants shifting to focus on development of small molecules targeting the crucial proteins of the viral replication machinery as effective therapeutic solutions. The PLpro is a crucial enzyme having multiple roles during the viral life cycle and a well-established drug target. In this study, we identified 12 potential inhibitors of PLpro through virtual screening of the FDA-approved drug library. Docking and molecular dynamics simulation studies suggested that these molecules bind to the PLpro through multiple interactions. Further, IC50 values obtained from enzyme-inhibition assays affirm the stronger affinities of the identified molecules for the PLpro. Also, we demonstrated high structural conservation in the catalytic site of PLpro between SCoV-2 and HCoV-229E through molecular modelling studies. Based on these similarities in PLpro structures, and the resemblance in various signalling pathways for the two viruses, we propose that HCoV-229E as a suitable surrogate for SCoV-2 in drug-discovery studies. Validating our hypothesis, Mefloquine, which was effective against HCoV-229E, was found to be effective against SCoV-2 as well in cell-based assays. Overall, the present study demonstrated that Mefloquine is a potential inhibitor of SCoV-2 PLpro, and its antiviral activity against SCoV-2. Corroborating our findings, based on the in vitro virus inhibition assays, a recent study reported a prophylactic role for Mefloquine against SCoV-2(1). Hence, Mefloquine may further be investigated for its potential as a drug candidate for the treatment of COVID.